PENGARUH PARTISIPASI PENGANGGARAN, ASIMETRI INFORMASI, DAN BUDAYA ORGANISASI PADA SENJANGAN ANGGARAN - Maharani, Anak Agung Istri; Agus Ardiana, Putu (E-Jurnal Akuntansi, 2015)
Budgeting has an impact on human behavior such as the creation of budgetary slack. Budgetary slack is the difference between the stated budget and honestly the best estimate that can be predicted . The study aims to determine the effect of budget participation , information asymmetry , as well as organizational culture on budgetary slack in Badung regency Credit Unions . In order to achieve this goal of data analysis techniques used multiple linear regression , test F - test and t test. Data collection method used here is based on questionnaires, distributed to administrators , managers , and members of credit unions in Badung . Based on the results of analysis of budget participation and information asymmetry positive effect on budgetary slack in savings and credit cooperatives in Badung while organizational culture had no effect on budgetary slack in savings and credit cooperatives in Badung .
Keywords: Budget Participation, Information Asymmetry, Organizational Culture, Budgetary Slack.